Music Playing and Interhemispheric Communication: Older Professional Musicians Outperform Age-Matched Non-Musicians in Fingertip Cross-Localization Test. (24th March 2021) - Piccirilli, Massimo; Palermo, Maria Teresa; Germani, Alessandro; Bertoli, Maria Laura; Ancarani, Viola; Buratta, Livia; Dioguardi, Maria Stefania; Scarponi, Laura; D'Alessandro, Patrizia
Abstract: Objective: Numerous investigations have documented that age-related changes in the integrity of the corpus callosum are associated with age-related decline in the interhemispheric transfer of information. Conversely, there is accumulating evidence for more efficient white matter organization of the corpus callosum in individuals with extensive musical training. However, the relationship between making music and accuracy in interhemispheric transfer remains poorly explored. Methods: To test the hypothesis that musicians show enhanced functional connectivity between the two hemispheres, 65 professional musicians (aged 56–90 years) and 65 age- and sex-matched non-musicians performed the fingertip cross-localization test. In this task, subjects must respond to a tactile stimulus presented to one hand using the ipsilateral (intra-hemispheric test) or contralateral (inter-hemispheric test) hand. Because the transfer of information from one hemisphere to another may imply a loss of accuracy, the value of the difference between the intrahemispheric and interhemispheric tests can be utilized as a reliable measure of the effectiveness of hemispheric interactions. Results: Older professional musicians show significantly greater accuracy in tactile interhemispheric transfer than non-musicians who suffer from age-related decline. Conclusions: Musicians have more efficient interhemispheric communication than age-matched non-musicians. This finding is in keeping with studies showing that individuals with extensive musical training have a larger corpus callosum. The results are discussed in relation to relevant data suggesting that music positively influences aging brain plasticity.